Assessing the context effect in emotion recognition of facial expression in the parafovea - Yu, Junming (Nanyang Technological University, 2025)
Previous study demonstrated the face context effect, in which participants’ emotion judgments of a target facial expression were positively biased toward the emotions of surrounding faces. The face context effect has been attributed to perceptual averaging between target and flanking face’s emotional expression and is understudied in the parafovea. It is unclear whether the negative emotion will constrain the context effect due to its reduced processing efficiency in the parafovea or intensify the context effect by attracting more attention resources. Here, we aimed to explore this question by presenting the target and flanking face in the parafovea and manipulated the emotional intensity of both flanking and target faces. Participants judged whether the target face’s emotional expression is sad or neutral in an emotion discrimination task. By fitting data to psychometric function at the group level, we found that the face context effect occurred when flanking faces were neutral but not when they were sad in parafoveal visual field. Individual differences of the face context effect was revealed by performing bootstrap analysis individually. Further analysis of “Sadness” response proportions at separate target emotion levels showed that the face context effect was most significant when emotion of target face is ambiguous (in the middle of the neutral-to-sad scale) and that target-flanker difference in emotion intensity positively predicts the face context effect. The absence of face context effect for sad flanking faces suggests that the averaging perception of faces in the parafovea is limited by processing efficiency of single face and contradicts with the attention account of averaging processing. The implications of these findings are significant for real-life scenarios in which people rely on contextual information from surrounding faces to judge the emotions of others when not looking directly at them, such as during group negotiation and public speaking.